Analysis of Plugging Effect for Open-Ended Piles in Sandy Soil - Sangseom Jeong; Junyoung Ko; Moonkyung Chung (Deep Foundations Institute, 2014)
"Abstract The plugging effect of open-ended piles in sandy soil is analyzed by full-scale field test and plugging measurement. PLR (plug length ratio) measurement data from 144 field cases are analyzed with pile diameter. Based on the plugging measurements, PLR of open-ended piles which have above 1000mm diameter is predicted to be above 0.9. Through plugging measurements, a new empirical method is suggested for quantifying the plugging effect of open-ended piles. The proposed PLR equation is possible to predict the behavior of soil plug in the preliminary design stage. In addition, in order to investigate the behavior of the soil plug of open-ended pile, field load tests are performed on instrumented three piles driven into sand. It is obtained that the resistance components of open-ended pile are separated by double-walled pile system. It is found that inner shaft capacity is developed nearby pile tip. However, upper soil plug did not influence the inner shaft capacity. Also, it is found that all test piles are floating piles and unplugged condition because the sum of inner shaft capacity and outer shaft capacity is calculated about 58 to 76% of the ultimate bearing capacity.INTRODUCTIONIn Korea, a number of huge construction projects such as harbor terminals, offshore grand bridges, and lifeline systems are progress in urban and costal area. In these areas, steel pipe piles are frequently used to support high-rise buildings and heavy weight structures for ensuring structural safety rather than serviceability limit capacity. Also, steel pipe piles are frequently used in civil engineering structures because they have many advantages such as high-load bearing capacity, light weight and outstanding workability. The mega foundations of grand bridges and high-rise buildings are required in geotechnical engineering. Large diameter driven piles are frequently used in several projects.Many specifications such as API, FHWA and AASHTO have been reported as a design guideline of plugging effect, however , the current design method for plugging effect of steel pipe piles are mainly based on the our knowledge derived from observation of the model test or the small diameter pile load test. Therefore, these specifications have limitation to apply the large diameter steel pipe piles.Much work has been done to study the plugging effect by many researchers. Yamahara (1964) reported that soil plug has been modeled as a thin disk element as shown in Figure 1, since the increment of radial strain of the soil plug can be neglected due to high rigidity of the pile compared to that of the soil plug. Klos and Tejchman (1977) reported that the end bearing capacity of open-ended piles was almost equal to that of a closed-ended pile when penetration depth of pile was above 15times the pile diameters by model tests. Paikowsky and Whitman(1990) reported fundamental studies on mechanism of plugging effect in sand. Paik et al. (2003) reported that empirical relations for plug load capacity, annulus load capacity, and shaft load capacity of open-ended piles are proposed based on the model pile tests. As discussed above, much work has been done in the area of plugging effect. But little work has been done to study the plugging effect by full scale field tests."